The role of VANGL2 in glioma oncogenesis and progression: insights into expression profiles and prognostic relevance - Zhao, Mingyu; Chen, Shanshuang (Frontiers in Oncology, 2025)
IntroductionThe Wnt/planar cell polarity (PCP) signaling pathway is pivotal in regulating various biological processes such as early embryonic development, neural crest cell migration, and cancer invasion. Despite advances in understanding the role of Wnt/PCP pathway dysregulation in tumorigenesis, numerous unanswered questions remain. Our study focused on VANGL2, a core PCP gene, to elucidate its potential mechanistic involvement in cancer development.MethodsA systematic analysis was conducted to assess VANGL2 expression patterns at both transcriptional and proteomic levels. Functional enrichment analysis was performed to investigate the biological pathways associated with VANGL2 in glioma. In vitro experiments were conducted to assess the impact of VANGL2 on glioma cell behaviors. Furthermore, rigorous methodologies were employed in survival analysis to control for confounding factors.ResultsWe identified substantial upregulation of VANGL2 gene in both low-grade glioma (LGG) and glioblastoma (GBM). Functional enrichment analysis of genes positively associated with VANGL2 in glioma underscored their enrichment in Notch signaling and pathway regulating pluripotency of stem cells. In vitro experiments further confirmed that VANGL2 promotes glioma cell migration, invasion, proliferation, and tumor sphere formation. We identified a significant correlation between increased VANGL2 expression and IDH mutation in glioma patients. Elevated VANGL2 expression was identified as a predictor of poor prognosis in glioma.ConclusionOur analysis of the expression and prognostic features of the core PCP gene VANGL2 underscored its critical roles in glioma oncogenesis and progression.